Factors affecting exercise intensity in rugby-specific small-sided games - Kennett, D. C.; Kempton, T.; Coutts, A. J. (The Journal of Strength and Conditioning Research, 2012)
Small-sided games (SSGs) have been suggested as a method for concurrently training physical, technical and tactical capabilities of rugby union players. Therefore, it is important to understand how prescriptive variables such as player number and field size influence the training stimulus during rugby-specific SSGs. Twenty semiprofessional rugby union players participated in a series of SSGs of varying player numbers (4 vs. 4, 6 vs. 6, and 8 vs. 8) on small- (32 × 24 m) and large-sized fields (64 × 48 m). The physiological (blood lactate concentration and heart rate [HR]), perceptual (rating of perceived exertion [RPE]), and time-motion demands were assessed for each different SSG format. There were significant differences between the 4 vs. 4, 6 vs. 6, and 8 vs.8 SSG formats in mean speed (meters per minute), high-speed running (HSR) distance (meters), and RPE (all p < 0.05). Blood lactate was greater in 4 vs. 4 compared with that in 8 vs. 8 SSGs. The mean speed, HSR distance, number of sprints, peak speed, blood lactate concentration, and RPE were all significantly different between large- and small-field size (all p < 0.05). There were no significant difference between game formats (4 vs. 4, 6 vs. 6, and 8 vs. 8) or field size (small or large) for either percent HRmax or time spent >85% HRmax. These results show that SSGs with fewer players and larger field sizes elicit greater physiological and perceptual responses and time-motion demands. In contrast, the HR response was similar between all SSG formats, which may be attributable to high levels of individual variability in the HR response. This study provides new information about the influence of player number and field size on the training stimulus provided by rugby-specific SSGs.